1996
DOI: 10.1089/ten.1996.2.61
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dynamic Compressive Loading on Biodegradable Implants of 50–50% Polylactic Acid–Polyglycolic Acid

Abstract: Biodegradable implants that release growth factors or other bioactive agents in a controlled manner are investigated to enhance the repair of musculoskeletal tissues. In this study, the in vitro release characteristics and mechanical properties of a 50:50 polylactic acid/polyglycolic acid two phase implant were examined over a 6-week period under no-load conditions or under a cyclic compressive load, such as that experienced when walking slowly during rehabilitation. The results demonstrated that a cyclic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 30 publications
2
22
0
2
Order By: Relevance
“…When there is insufficient flow to drain the acidic degradation products from the matrix, the rate of degradation is thus enhanced [1, 3, 45]. Likewise, PLA devices degrade faster when they are less porous [2], less permeable [81], have a bulkier de- sign [39], and function under static loading conditions [1,97]. Due to these many factors, it is difficult to predict degradation kinetics of a device in a particular application, even if an identical, well characterized, material is used.…”
Section: Degradationmentioning
confidence: 99%
“…When there is insufficient flow to drain the acidic degradation products from the matrix, the rate of degradation is thus enhanced [1, 3, 45]. Likewise, PLA devices degrade faster when they are less porous [2], less permeable [81], have a bulkier de- sign [39], and function under static loading conditions [1,97]. Due to these many factors, it is difficult to predict degradation kinetics of a device in a particular application, even if an identical, well characterized, material is used.…”
Section: Degradationmentioning
confidence: 99%
“…Results also demonstrated that cyclic compressive loading significantly slowed the decrease of molecular chain size during the first week, significantly increased protein release for the first 2-3 weeks, and significantly stiffened the implant for the first 3 weeks. In addition, this study showed that dynamic loading and the environment in which an implant was placed affect its biodegradation [27]. By providing a greater understanding of the degradation properties of PLGA, these studies provided a foundation for future in vivo studies.…”
Section: Biodegradable Scaffoldsmentioning
confidence: 83%
“…It has been well reported that the mechanical stimuli altered the physiological behaviors of cells [1,2] and mediated the scaffold degradation [3,4].…”
Section: Introductionmentioning
confidence: 99%